Synthesis, characterization and photocatalystic activity of multiwalled carbon nanotubes/titanium dioxide nanocomposite - Abdullahi, Nura (2015)
As a result of large band gap and high recombination of photo-generated electronsholes within nanoseconds, which limit the effectiveness of anatase-phase titanium dioxide (TiO2) semiconductor nanoparticle. Active MWCNTs/TiO2 nanocomposites were fabricated by dispersing TiO2 onto the surface of functionalized multiwalled carbon nanotubes (fMWCNTs) and used it as a hotocatalyst. The optical, structural,and morphological properties of the as-prepared MWCNTs/TiO2 nanocomposites were studied. The typical particle sizes between 30 and 36 nm were achieved by TEM. This was supported by the crystal sizes of 16, 14 and 13 nm for MWCNTs/TiO2 ratios of (1:3), (1:2), and (1:1) respectively, evaluated from Shearer equation of the XRD spectra, which show the present of anatase and rutile states. The optical properties were characterized using UV-Vis reflection spectroscopy and found the band gap of 2.93, 2.86, and 2.75eV for MWCNTs/TiO2 ratios of (1:1),(1:2), and (1:3) respectively, calculated from Kubelka-Munk function. The PL peak intensity of TiO2 was higher for MWCNTs/TiO2 (1:3) as loading of TiO2 increased. The effect of the initial concentration of the methylene blue dye and pH of the medium were investigated on photocatalytic activity of the MWCNTs/TiO2 nanocomposites of the lowest band gap at the optimum mass ratio (1:3). It was found that the photodegradation followed the first order kinetics. The photocatalytic activity was found to increase with increase in the initial dye concentration after which it falls as the concentration of methylene blue is increased above optimum. At 30 min, 92.56 and 75.95% degradation efficiency were recorded for 10.2 and 7.0 pH solutions respectively. While in 1.9 pH solution, approximately 45.23% methylene blue degradation was recorded.